A Phenomenological Study of Toxic Relationships in Interpersonal Communication in Generation Z Women in West Bogor City - Deasti Lisna Pebriani (BINA: JURNAL PEMBANGUNAN DAERAH, 2024)
Communication will be effective if each other gives the desired feedback. Toxic relationships in interpersonal communication in adolescents cannot be said to have chosen healthier relationships because they or teenagers still like to feel each other. Interpersonal communication that is forged by adolescents in their peer environment can actually strengthen the development of a teenager's identity. This study aims to analyze the phenomenon of toxic relationships in interpersonal communication in women of generation Z and to determine the impact of toxic relationships experienced by women of generation Z. This research uses a qualitative descriptive method that is as it is and is carried out through observation, in-depth interviews, and documentation with reliable data sources. derived from data and secondary. Researchers use the theory of Interpersonal Communication Effectiveness which is divided into five parts, namely Openness, Empathy, Support, Positiveness, and Equality. The results of this study indicate that the phenomena and impacts of toxic relationships on generation Z women are physical impacts, economic impacts, social impacts, and also psychological impacts. Other findings from this study indicate that toxic relationship couples prefer to survive in arguments because they already love each other, are already close to each other, have a fear of losing and are afraid of not being accepted by others because they have had sexual relations with their partners.Keywords: interpersonal communication, woman, toxic relationship